Bringing Morality Back in: Institutional Theory and MacIntyre. (April 2017) - Moore, Geoff; Grandy, Gina
This article sets out to explore the extent to which the moral dimension is an essential component in organizational life. From a theoretical viewpoint, it argues that institutional theory lacks a positive account of the role of morality at the organizational level. We propose that this can be addressed by integrating the work of the moral philosopher Alasdair MacIntyre with institutional theory's notions of logics, contradictions, and legitimacy. Empirically, we look to a group of Christian churches in the northeast of England to provide insights into practitioners' concerns with the telos of their organizations and the core practices of their faith, and hence of an essential concern for the morality of organizational life. We conclude that any understanding of practice-based organizations that ignores or underplays the moral dimension will give, at best, a diminished account of organizational life, and hence that institutional theory needs to rethink its neglect of morality.